1994
DOI: 10.1152/jn.1994.72.3.1192
|View full text |Cite
|
Sign up to set email alerts
|

Substance P elevates intracellular calcium in both neurons and glial cells from the dorsal horn of the spinal cord

Abstract: 1. We used microfluorimetric measurement of [Ca2+]i to identify substance P-sensitive cells acutely isolated from the dorsal horn of neonatal rats. We then used morphological, physiological, and immunocytochemical criteria to delineate two distinct populations of substance P-sensitive dorsal horn cells. 2. One population of cells with small-diameter cell bodies and many fine processes responds to substance P by releasing Ca2+ from internal stores. Many of these cells express the O4 surface antigen, and are thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…SP plays dual roles in spinal nociceptive transmission as a transmitter of primary afferent fibers and a modulator of local and descending pathways. It is known that the activation of the NK1 receptor increases intracellular calcium concentrations (Shen and North, 1992;Otsuka and Yoshioka, 1993;Heath et al, 1994). In the present study, we found that SP activated Erk in spinal dorsal horn neurons, and a selective NK1 receptor antagonist could block the effect of SP.…”
Section: Discussionsupporting
confidence: 60%
“…SP plays dual roles in spinal nociceptive transmission as a transmitter of primary afferent fibers and a modulator of local and descending pathways. It is known that the activation of the NK1 receptor increases intracellular calcium concentrations (Shen and North, 1992;Otsuka and Yoshioka, 1993;Heath et al, 1994). In the present study, we found that SP activated Erk in spinal dorsal horn neurons, and a selective NK1 receptor antagonist could block the effect of SP.…”
Section: Discussionsupporting
confidence: 60%
“…Ca 2ϩ imaging with the Ca 2ϩ indicator dye fura-2 (Grynkiewicz et al, 1985) was used to perform the pharmacological testing because it provides a way to scan rapidly a field of neurons and to detect the minority of cells sensitive to ATP. Neuronal identity was confirmed by morphology and sensitivity to 100 M NMDA (Heath et al, 1994). E xogenously applied ATP (100 M) elevated intracellular Ca 2ϩ concentration ([C a 2ϩ ] i ) in a small subpopulation (Ͻ5%) of acutely dissociated dorsal horn neurons (Fig.…”
Section: P 2x Receptor Activation Measured By Calcium Imaging and Whomentioning
confidence: 90%
“…These findings indicate that SP could be involved in a seizure-induced cell death pathway involving bax and caspases. SP, while increasing intracellular Ca 2ϩ (6) and enhancing glutamate responses (7,8) or glutamate release (9,38), may induce expression and activation of bax (39) and caspase 3 (31). Activation of bax may trigger the release of cytochrome c and other proteins from the mitochondria and induce caspase activation in cytosol (26,27).…”
Section: Discussionmentioning
confidence: 99%